Beam dynamics in a customs cyclotron with an internal ion source - Samsonov, E.V.; Onischenko, L.M.; Vorozhtsov, A.S. (Вопросы атомной науки и техники, 2006)
A project of a complex for explosives detection on a base of a gamma resonance method is developed in Russia.
The search for explosives is based on the detection of high nitrogen concentrations in a luggage. The complex consists
of a cyclotron, developed in Dubna, an original storage ring, a gamma rays producing 13C target, and a detecting
equipment. For purposes of simplification in the cyclotron design an internal source of H⁻ ions instead of an external
beam injection was introduced and examined. The computations have shown that the beam with an energy
~1.8 MeV and current 100…200 μA would be extracted from the cyclotron with efficiency ~95%. Проект комплекса для обнаружения взрывчатых веществ на базе гамма-резонансного метода разрабатывается в России. Поиск взрывчатки основан на детектировании высоких концентраций азота в объектах багажа. Установка состоит из циклотрона, который разрабатывается в Дубне, небольшого накопительного кольца, гамма-мишени и детектирующей аппаратуры. В целях упрощения конструкции циклотрона используется внутренний источник Н⁻ ионов вместо их аксиальной инжекции. Расчеты показывают, что пучок с энергией ~1.8 МэВ и током 100...200 мкА может быть выведен из циклотрона с эффективностью ~95%. Проект комплексу для виявлення вибухових речовин на базі гамма-резонансного методу розробляється в
Росії. Пошук вибухівки заснований на детектуванні високих концентрацій азоту в об'єктах багажу.
Установка складається із циклотрона, що розробляється в Дубні, невеликого накопичувального кільця,
гамма-мішені і апаратури для детектування. З метою спрощення конструкції циклотрона використано внутрішнє джерело Н⁻ іонів замість їхньої аксіальної інжекції. Розрахунки показують, що пучок з енергією ~1.8 МеВ і струмом 100...200 мкА може бути виведений із циклотрона з ефективністю ~95%.